Ustification of the parameters for setting up operations of through-pass centerless grinding - V. Malinin, Pavel; Yu. Bochkarev, Petr; I. Artemov, Igor'; O. Goncharov, Mikhail (Известия высших учебных заведений. Поволжский регион:Технические науки, 2024)
Background. The insufficiently widespread use of centerless grinding methods, characterized by high productivity and the quality of the treated surfaces, in modern production is due to insufficient scientific study of certain issues of setting up technological operations. In this regard, it is urgent to develop the scientific base created by domestic scientists and specialists. Materials and methods. The results of a survey of advanced enterprises in the Volga region on issues related to the implementation of procedures for setting up centerless grinding equipment are presented and systematized. Models and an algorithm for determining the adjustment parameters are presented, taking into account the actual dimensional characteristics of grinding and driving wheels, and the sizes of workpieces. The adjustment parameters are proposed, which can be regulated using the working bodies of the equipment, which increases the objectivity of the quality of work and reduces the complexity of the equipment adjustment procedure. Results. The results of the experiments confirmed the relationship between the real dimensional characteristics of the elements of the technological system and their influence on the purpose of the adjustment parameters. Conclusions. The developed methods make it possible to eliminate the subjective factor of the process of equipment setup and implementation management, which makes it possible to increase the efficiency of through-pass centerless grinding operations.